Alternatively Activated Macrophages Revisited: New Insights into the Regulation of Immunity, Inflammation and Metabolic Function following Parasite Infection - C. Jang, Jessica; G. Nair, Meera (Current Immunology Reviews (Discontinued), 2013)
The role of macrophages in homeostatic conditions and the immune system range from clearing debris to recognizing and killing pathogens. While classically activated macrophages (CAMacs) are induced by T helper type 1 (Th1) cytokines and exhibit microbicidal properties, Th2 cytokines promote alternative activation of macrophages (AAMacs). AAMacs contribute to the killing of helminth parasites and mediate additional host-protective processes such as regulating inflammation and wound healing. Yet, other parasites susceptible to Th1 type responses can exploit alternative activation of macrophages to diminish Th1 immune responses and prolong infection. In this review, we will delineate the factors that mediate alternative activation (e.g. Th2 cytokines and chitin) and the resulting downstream signaling events (e.g. STAT6 signaling). Next, the specific AAMac-derived factors (e.g. Arginase1) that contribute to resistance or susceptibility to parasitic infections will be summarized. Finally, we will conclude with the discussion of additional AAMac functions beyond immunity to parasites, including the regulation of inflammation, wound healing and the regulation of metabolic disorders.
Keywords: Th2 inflammation